APLIKASI E-DIAGNOSIS PENYAKIT ENDIMIK BERBASIS ANDROID MENERAPKAN METODE OPTIMASI NAÏVE BAYES - Hadiyansyah Hadiyansyah; Diana Diana (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2022)
Lack of public understanding of endemic diseases can increase the number of sufferers. This study aims to build an e-diagnosis application to determine the type of endemic disease using the Naïve Bayes Optimization method. This application will be able to provide information about the disease suffered by the patient based on the symptoms entered in the application. The information provided includes a description of the disease, its causes and solutions. The application development stage adopts the stages in the Expert System Development Life Cycle (ESDLC) which includes project initialization, knowledge engineering process and implementation. The application of the Naïve Bayes Oprimization method produces a diagnosis result in the form of the type of disease dan its opportunities. The application can accessed by the public anywhere and anytime because this application is based on Android. Utilization of android can optimze the use of this application.